2017
DOI: 10.1002/bem.22029
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 50 Hz electromagnetic fields on human epidermal stem cell transplantation seeded in collagen sponge scaffolds for wound healing in a murine model

Abstract: To explore the possible efficacy of electromagnetic fields (EMF) for skin tissue engineering, effects of EMF exposure on epidermal stem cells (ESC) seeded in collagen sponge scaffolds for wound healing in a murine model were investigated. The wound models of a full-thickness defect established with 36 7 ∼ 8-week-old nude mice were randomly divided into three groups: a control group, an ESC-only group, and an ESC with EMF exposure group (frequency of 50 Hz, magnetic induction of 5 mT, 60 min per day for 20 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…During the process of proliferation and differentiation of basal-layer cells, the expression of the surface integrin is gradually downregulated until it disappears, and the cells gradually migrate to the surface of the skin and are finally keratinized and exfoliated. Studies have demonstrated [16][17][18] that the decrease in β1 integrin expression stimulates hair follicle stem cells to leave the stem cell pool and migrate upward into differentiated cells [19,20]. Moreover, some researchers have found that nitric oxide (NO) can mediate the regulation of β1 integrin expression, affect the proliferation and differentiation of EpiSCs through cGMP signaling pathway, and then participate in the process of wound healing [21].…”
Section: Integrinmentioning
confidence: 99%
“…During the process of proliferation and differentiation of basal-layer cells, the expression of the surface integrin is gradually downregulated until it disappears, and the cells gradually migrate to the surface of the skin and are finally keratinized and exfoliated. Studies have demonstrated [16][17][18] that the decrease in β1 integrin expression stimulates hair follicle stem cells to leave the stem cell pool and migrate upward into differentiated cells [19,20]. Moreover, some researchers have found that nitric oxide (NO) can mediate the regulation of β1 integrin expression, affect the proliferation and differentiation of EpiSCs through cGMP signaling pathway, and then participate in the process of wound healing [21].…”
Section: Integrinmentioning
confidence: 99%
“…Microglia autophagy serve an important role in the differentiation, survival and homeostasis maintenance of transplanted stem cells (43)(44)(45)(46). Previous studies have demonstrated that bone marrow-derived neural progenitor cells can differentiate into neurons and their transplantation in vivo can effectively promote the motor function of rats following brain injury (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and culture of bone marrow-derived neural progenitor cells. The methods and procedures for the isolation, culture and identification of bone marrow-derived neural progenitor cells were performed based on previous studies (25)(26)(27). Three Sprague-Dawley rats (sex, male; age, 5 weeks; weight, 115-150 g) were housed in a temperature of 18-25˚C and 30-60% humidity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations